A laboratory for Latin eugenics: the Italian Committee for the Study of Population Problems and the international circulation of eugenic knowledge, 1920s-1940s - Luc André Berlivet (História, Ciências, Saúde: Manguinhos)
Abstract The aim of this article is to shed light on the rise to international prominence of the Italian statistician and eugenicist Corrado Gini and his appointment as the inaugural president of the Latin International Federation of Eugenic Societies in October 1935. It explores the numerous pioneering, still little known, investigations he undertook with a few Italian scientists and some foreign scholars, in order to analyze the role played by “isolation,” and “racial hybridization” in the formation and degeneration of human races. After outlining Gini’s professional and political trajectory, the article focuses on the scientific expeditions launched by the Italian Committee for the Study of Population Problems between 1933 and 1940 under his stewardship.